Getting clean and harm reduction: adversarial or complementary issues for injection drug users - James Peterson; Shannon Gwin Mitchell; Yan Hong; Michael Agar; Carl Latkin (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
Many contemporary HIV prevention interventions targeting injection drug users (IDUs) have been implemented using Harm Reduction as a theoretical framework. Among drug-using individuals, however, the abstinence-based "getting clean" models espoused by Narcotics Anonymous and other widely adopted approaches to drug treatment are often more readily accepted. This paper describes an ethnographic examination of the ideological dichotomy between Harm Reduction and abstinence-based "getting clean" treatment model which emerged during the piloting phase of an HIV prevention intervention in Baltimore City, Maryland, USA. This paper describes how the conflict was identified and what changes were made to the intervention to help resolve the participants' dichotomous thinking concerning their substance abuse issues.